2012
DOI: 10.4103/1947-2714.93377
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women and non-steroidal anti-inflammatory drugs: Knowledge, perception and drug consumption pattern during pregnancy in Ethiopia

Abstract: Background:Non-steroidal anti-inflammatory drugs (NSAIDs) are among the widely used drugs and are often used by pregnant women. However, they can have significant teratogenic effects. The aim of the study was to investigate pregnant women's knowledge about NSAIDs use during pregnancy and their perception and consumption pattern.Materials and Methods:The study was a cross sectional study on women waiting for a consultation in the selected maternity hospitals in Addis Ababa, Ethiopia. The pregnant women were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Analgesic drug use is high, with more than half (55.1%) of the pregnant women using paracetamol during the study period. This is consistent with the findings from Pakistan (43.6%) [ 13 ] and Ethiopia (37.5%) [ 31 ]. It is common knowledge that every drug incurs a side effect within the human body which is consistent with the finding that paracetamol might have an adverse effect on neurological development (psychomotor, behavioral, and temperamental outcomes for the child), irrelevant of the trimester exposure that took place [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Analgesic drug use is high, with more than half (55.1%) of the pregnant women using paracetamol during the study period. This is consistent with the findings from Pakistan (43.6%) [ 13 ] and Ethiopia (37.5%) [ 31 ]. It is common knowledge that every drug incurs a side effect within the human body which is consistent with the finding that paracetamol might have an adverse effect on neurological development (psychomotor, behavioral, and temperamental outcomes for the child), irrelevant of the trimester exposure that took place [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In Ethiopia on the other hand, nearly 90% of the pregnant women had used NSAIDs. 35 Despite the fact that NSAIDs may have a deleterious effect on the foetus, quite a significant number pregnant women still take these medications in pregnancy. According to research, NSAIDs, such as diclofenac increases the risks of miscarriage and malformations in early pregnancy and in the third trimester, can cause early closure and constriction of ductus arteriosus with subsequent neonatal pulmonary hypertension and transient right-sided hypertrophic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that pregnant women in developing countries frequently take medication by themselves due to the lack of knowledge and awareness about medication [ 7 – 9 ]. It is essential to help healthcare professionals identify the gaps to improve pregnant women’s understanding of medication use and safety during pregnancy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%